On binary opposition and binarism: A long-distance dialogue between decolonial critique and the Lotmanian semiotics - Gherlone, Laura (2023)
While addressing the decolonial critique of Eurocentric modernity and the call for alternative cosmo-visions, this article retraces Juri Lotman’s culturological exploration towards the concept of ternarity [тернарность]: the scrutiny of the so-called binarism is what connects – without overlapping – the two perspectives. This long-distance dialogue will be built starting with the key notion of binary opposition, which will be analysed as a decolonial problem (Part I) and as a culturological problem (Part II). The analysis will focus on two central issues that stem from the either-or logic: the “othering mindset”, and the culture–nature dualism.